(untitled) (The Research of Medical Science Review, 2025)
Back ground: Patient satisfaction is the assessment of patient consent after receiving health care. Or the patient’s satisfaction is the assessment of the contentment of health care Receiver in the middle of health caring. Methodology: We conducted an observational study with cross sectional approach from Dec 2023 to Jan 2024 in four teaching hospitals i.e. Nangarhar University teaching hospital(NUTH), Spinghar Momand Teaching Hospital(SMTH), Roshan Teaching Hospital(RTH) and Aryana Danishmal Teaching Hospital(ADTH) across Jalal Abad City. A Cluster sampling method used to assess patient satisfaction in overall 322 OPD patients by standard PSQ-18 questionnaire conveniently. Results: Total of 322 patients (255 from public 77 from private) were cluster based interviewed according to the number of theirs last year OPD visits. Overall satisfaction among 322 participants were [88.07 %( 4.40±0.12)]. We observed variation across seven dimensions. The overall satisfaction in NUTH was [89% (4.45±0.74)]. The highest rate of satisfaction was about Interpersonal manner [94.2 %( 4.71±0.67)] and the least satisfaction was about Accessibility & convenience [81.8 %( 4.09±0.8)]. At SMTH the overall satisfaction was [87.2% (4.36±0.6)]. The highest rate of satisfaction was about Time spent with doctor [96.6 %( 4.83±0.46)] and the least satisfaction was about General satisfaction [81.2 %( 4.06±0.7)]. In RTH overall satisfaction was [80.54 %( 4.02±0.74)]. The highest rate of satisfaction was about Time spent with doctor [94 %( 4.7±0.94)] and the lowest rate of satisfaction was about Financial aspect [54 %( 2.7 ±1.03)] and Accessibility and convenience [77.4 %( 3.87±0.84)]. Conclusion: We determined that patient satisfaction varied significantly across several dimensions in four hospitals (one public and three private). Patients expressed the least satisfaction in accessibility and convenience, General satisfaction, and financial aspect while showing high satisfaction in interpersonal interactions, and time spent white physician. Targeted initiatives aimed at enhancing the aspects of patient satisfaction in areas with low satisfaction levels are necessary. Regularly perform analogous investigations at diverse tiers of healthcare facilities nationwide to obtain a comprehensive understanding of patient satisfaction across different levels.